2015
DOI: 10.1016/j.cell.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Bunyavirus Replication and Its Regulation by the vRNA Promoter

Abstract: SummarySegmented negative-strand RNA virus (sNSV) polymerases transcribe and replicate the viral RNA (vRNA) within a ribonucleoprotein particle (RNP). We present cryo-EM and X-ray structures of, respectively, apo- and vRNA bound La Crosse orthobunyavirus (LACV) polymerase that give atomic-resolution insight into how such RNPs perform RNA synthesis. The complementary 3′ and 5′ vRNA extremities are sequence specifically bound in separate sites on the polymerase. The 5′ end binds as a stem-loop, allosterically st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
243
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(262 citation statements)
references
References 34 publications
11
243
2
Order By: Relevance
“…The RNA-dependent RNA polymerase catalytic domain of protein L Sequence analysis suggests that the N-terminal half of protein L functions as a RNA-dependent RNA polymerase (RdRP), and is responsible for both DNA replication and transcription. HHpred 45 detects the Bunyavirus RdRP (PDB id: 5AMR 83 ) as a structural template (Probability: 84%). The alignment between Ebolavirus RdRP and Bunyavirus RdRP includes both the catalytic domain and a helical bundle connected to its C-terminus.…”
Section: The Zinc-finger Domain Of Vp30mentioning
confidence: 99%
“…The RNA-dependent RNA polymerase catalytic domain of protein L Sequence analysis suggests that the N-terminal half of protein L functions as a RNA-dependent RNA polymerase (RdRP), and is responsible for both DNA replication and transcription. HHpred 45 detects the Bunyavirus RdRP (PDB id: 5AMR 83 ) as a structural template (Probability: 84%). The alignment between Ebolavirus RdRP and Bunyavirus RdRP includes both the catalytic domain and a helical bundle connected to its C-terminus.…”
Section: The Zinc-finger Domain Of Vp30mentioning
confidence: 99%
“…The binding of NP to the virus genome is required to form the vRNP template for an efficient elongation reaction by RdR Pol (8)(9)(10)(11)(12). A recent structural model of RdR Pol of a segmented negative-strand RNA virus led to the proposal that the disruption of the vRNP structure during template reading is restricted around the active center due to the proximity of the entry and exit channels of template (42). Based on these findings, it is possible that Prp18 functions as a molecular chaperone for NP around the active center of RdR Pol to maintain the structural integrity of vRNP for processive template reading.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, RdRps that initiate RNA synthesis at the NP gene start site and then cap the nascent NP mRNA become committed to transcription (23,24). Structural studies of both sNSV and nsNSV RdRps suggest that both can be found in a number of alternative states or conformations, each of which may be important during different steps of RNA synthesis (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%